A STUDY ON STUDENTS’ ABILITY IN READING COMPREHENSION OF RECOUNT TEXT AT SMPN 8 PEKANBARU - Abdillah, Bayu Syafiq; Prawati, Atni (Universitas PGRI Sumatera Barat, 2025)
This study aimed to assess the reading comprehension skills of eighth-grade students in understanding recount texts at SMPN 8 Pekanbaru. Using a quantitative method, data were collected through a multiple-choice test administered to 32 purposively selected students from class 8H. The analysis focused on six indicators: finding factual information, main ideas, references, word meanings, inferences, and language features. Results showed an average score of 70, indicating a good level of comprehension. Students performed best in identifying main ideas (81%), followed by references (79%), and both factual information and inferences (75%). Lower scores were seen in recognizing language features (64.37%) and understanding word meanings (49%). These findings provide insight into students’ strengths and challenges in reading comprehension of recount texts.